(untitled) (Tamaddun, 2022)
This research aimed at finding out whether or not the use of Plan-ahead Brainstorming in helping the second-year students of SMAN 1 Bantaeng to enhance their speaking skill. The steps of Plan-ahead Brainstorming in implementing consist of (1) giving the topic, (2) plan-ahead session, (3) brainstorming in small group, (4) individual oral report. This research employed pre-experimental method. The researcher used random sampling technique and the selected sample was the students in XI IPA1 with the total 28 number of students. The instrument of this research was speaking test in the form of oral test. The data acquired were then analyzed through descriptive and inferential statistics. The result of the data analysis showed that the probability value (0.00) was smaller than the level of significance (0.05). This indicated that the implementation of Plan-ahead Brainstorming enhanced the students` speaking skill. This indicates that the alternative hypothesis (H1) accepted. This research contributed extensively the theory about plan-ahead brainstorming in enhancing students speaking ability. The plan-ahead brainstorming is the technique that can influence the students speaking fluency effectively. The outcome of the use of plan-ahead brainstorming is useful in learning English, especially students in learning speaking. The student can decrease their skepticism and stammer in plan-ahead session to prepare what they want to utter. The researcher found that this technique is useful for teachers in order that they can use this technique more effectively as long as the teacher prepare specific time to implement this technique in several time.